Glomerulotubular pathology in dogs with subclinical ehrlichiosis - Crivellenti, Leandro Zuccolotto; Cintra, Cristiane Alves [UNESP]; Maia, Suellen Rodrigues [UNESP]; Silva, Gyl Eanes Barros; Borin-Crivellenti, Sofia; Cianciolo, Rachel; Adin, Christopher A.; Tinucci-Costa, Mirela [UNESP]; Pennacchi, Caio Santos; Santana, Aureo Evangelista [UNESP] (Public Library of Science (PLoS), 2021)
Subclinical stage of ehrlichiosis is characterized by absence of clinical or laboratory alterations; however, it could lead to silent glomerular/tubular changes and contribute significantly to renal failure in humans and animals. The aim of this study was to evaluate glomerular and tubular alterations in dogs with subclinical ehrlichiosis. We evaluated renal biopsies of 14 bitches with subclinical ehrlichiosis and 11 control dogs. Samples were obtained from the left kidney, and the tissue obtained was divided for light microscopy, immunofluorescence, and transmission electron microscopy. Abnormalities were identified by light microscopy in 92.9% of dogs with ehrlichiosis, but not in any of the dogs of the control group. Mesangial cell proliferation and synechiae (46.1%) were the most common findings, but focal segmental glomerulosclerosis and ischemic glomeruli (38.4%), focal glomerular mesangial matrix expansion (30.7%), mild to moderate interstitial fibrosis and tubular atrophy (23%), and glomerular basement membrane spikes (23%) were also frequent in dogs with ehrlichiosis. All animals with ehrlichiosis exhibited positive immunofluorescence staining for immunoglobulins. Transmission electron microscopy from dogs with ehrlichiosis revealed slight changes such as sparse surface projections and basement membrane double contour. The subclinical phase of ehrlichiosis poses a higher risk of development of kidney damage due to the deposition of immune complexes.